MO783: Reduction of the Incidence of Dialysis Catheter-Associated Bacteraemia in Intensive Care Units after Systematic Application of Taurolock in the Sealing of the Catheter. (3rd May 2022) - Del Risco Zevallos, Jimena; Molina-Andujar, Alicia; Piñeiro, Gaston; Fernando Quintana Porras, Luis; Blasco, Miquel; Morata, Laura; Soriano, Alex; Poch, Esteban
Abstract: BACKGROUND AND AIMS: Dialysis catheter-associated bacteraemia in Intensive Care Units (ICUs) increases morbidity and mortality, prolongs hospital admission and increases admission costs. TauroLock™ is a lock solution containing (cyclo)-taurolidine (1.35%) and citrate (4%). (Cyclo)-taurolidine has broad antimicrobial activity against gram-positive and gram-negative bacteria and fungi. The objective of this study was to analyse the effect of systematic sealing of haemodialysis catheters in the ICUs of the Hospital Clínic de Barcelona on the incidence of bacteraemia associated with haemodialysis catheters (BACH). METHOD: BACH episodes of patients who underwent intermittent haemodialysis (IHD) during ICU admission were reviewed. The period analysed as pre-Taurolock™ was from 2010 to 2014 and post-TauroLock™ from 2015 to 2018. Patients who only received renal replacement therapy with continuous techniques were excluded. RESULTS: A total of 279 patients received IHD in the pre-TauroLock™ period and 331 in the post-TauroLock™ period. The number of BACH in the pre-TauroLock™ period was 18 (6.45%) and 9 (2.72%) in the post-TauroLock™ period. All infections were from percutaneous catheters (acute patients) except three catheters that were tunnelled. In the pre-TauroLock™ period, femoral catheters predominated (61.1%) while in the post-TauroLock they were jugular (66.7%). There was no association between the location of the catheter and the incidence of BACH. Of the 27 patients with BACH, 14 (51.8%) were men with a mean age of 63 years, with no significant differences between the two groups. The most frequent reasons for admission to the ICU in the pre-TauroLock™ period were post-cardiac surgery, cardiogenic, septic or hypovolemic shock and acute myocardial infarction (3 patients per group) and in the post-TauroLock™ period, septic shock and pancreatitis (3 and 2 patients respectively). The most frequent isolated bacteria were Gram-positive (in total 48.38%: pre-TauroLock™ 47.61% and post-TauroLock™ 50%), with a global predominance of staphylococcus epidermidis (32.25%) (Table ). There were no significant differences in the median days from the start of haemodialysis to bacteraemia (23.5 pre-TauroLock™ versus 21 post-TauroLock™). There were also no significant differences between the days of ICU stay in the BACH in both groups or in mortality, being the overall mortality of 70.4%. CONCLUSION: In our cohort, the systematic application of TauroLock™ in the sealing of dialysis catheters in critically ill patients reduces the incidence of BACH in ICUs.